Characterization of operating conditions of two residential wood combustion appliances - Calvo, A. I.
This work presents the main physical characteristics and operating conditions of a fireplace and a stove commonly used in Portugal for domestic heating based on biomass combustion. The fuel used was wood from pine (softwood) and eucalyptus (hardwood). The general trend during the batch combustion of wood logs was characterized by three main periods: i) a first period of fuel heating followed by fuel drying and initial steps of devolatilization without the existence of a visible flame, ii) a second period characterized by devolatilization, ignition, combustion of volatiles and char, during which a vigorous flame is observed, and iii) a third period, mainly identified by the combustion of the char, during which there are only localized small visible flames over the char particles. Each of these periods is characterized by specific fuel consumption rate, flue gas temperature and flue gas composition. The main differences between the wood combustion conditions in the fireplace and in the stove include: i) a lower flue gas temperature in the fireplace, ii) a higher combustion flue gas flow rate in the fireplace, iii) a higher rate of fuel consumption in the stove, and iv) higher CO, total hydrocarbon and particle emission factors during the combustion of wood in the fireplace. Differences between hardwood and softwood combustion were also pointed out.